RskA Is a Dual Function Activator-Inhibitor That Controls SigK Activity Across Distinct Bacterial Genera - Veyrier, Frédéric J.; Nieves, Cecilia; Lefrancois, Louise H.; Trigui, Hana; Vincent, Antony T.; Behr, Marcel A. (Frontiers in Microbiology, 2020)
It has been previously shown that RskA, the anti-Sigma factor K of M. tuberculosis, inhibits SigK and that mutations in RskA promote high expression of the SigK regulon. The latter observation led us to hypothesize that RskA mutations lead to loss of the anti-Sigma factor function. In this report, we used natural and artificial mutations in RskA to determine the basis of the SigK-RskA partnership. Consistent with predictions, the N-terminal cytoplasmic portion of RskA was sufficient on its own to inhibit SigK. Unexpectedly, RskA also served as an activator of SigK. This activation depended on the same N-terminal region and was enhanced by the membrane-extracellular portion of RskA. Based on this, we engineered similar truncations in a Gram-negative bacterium, namely Yersinia enterocolitica. Again, we observed that, with specific alterations of RskA, we were able to enhance SigK activity. Together these results support an alternative mechanism of anti-Sigma factor function, that we could term modulator (activator-inhibitor) in both Actinobacteria and Gram-negative bacteria, suggesting that Sigma factor activation by anti-Sigma factors could be under-recognized.